Implementation of No-Code App Builders in Developing Mobile Applications for Micro, Small, and Medium Enterprises (MSMEs) - Sarini, Sarini (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This study examines the implementation of No-Code App Builders as a digital solution for empowering Micro, Small, and Medium Enterprises (MSMEs) in Aceh. The research applied a qualitative descriptive approach combined with prototype testing to evaluate the usability and practicality of No-Code platforms, particularly Kodular and Airtable, in supporting small business operations. The prototype was developed to manage key functions such as product cataloging, order processing, and sales monitoring. Ten MSME owners participated in the testing phase, representing various sectors including food production, handicrafts, and retail. The results showed that participants could operate the system independently after a brief introduction, with an average task efficiency improvement of 40 percent compared to manual methods. Users reported high satisfaction with the interface design, while minor issues in data input were resolved through iterative refinement. The findings confirm that No-Code App Builders effectively reduce dependency on professional developers and lower the technical and financial barriers that often limit digital participation among small enterprises. Beyond the technical outcomes, the approach fostered digital confidence, operational autonomy, and innovation among MSME owners. Strategically, the adoption of No-Code development models supports inclusive digital transformation and strengthens local economic resilience. The study recommends greater collaboration between universities, government institutions, and business networks to provide training, policy incentives, and sustainable support systems that encourage the widespread use of No-Code tools across regional MSMEs.